ISOLAMENTO DE NEOSPORA CANINUM DE BOVINOS E CARACTERIZAÇÃO BIOLÓGICA DE ISOLADOS EM CAMUNDONGOS BALB/c - MELO, Débora Pereira Garcia (2008)
The objective of this work was to obtain new isolates of N. caninum and characterize the same pathogenically. In Nerópolis (Goiás, Brazil), two Holstein-Friesian male calves, aged four months, positive for indirect immunoflourescence for Neospora with a titre of 1:400 and 1:800 were utilized for the isolation. Two new isolates, NC- Goiás 1 and NC-Goiás 2, were obtained. NC-Goiás 2 was discarded, however, due to fungal contamination. In addition to characterization of isolate NC-Goiás 1, pathogenic characterizations were done for six Spanish isolates in female mice of the lineage Balb/c. Symptomatology and mortality caused by the isolates, parasitaemia, detection of parasite DNA in the brain and lungs were verified, as well as parasite load in the brain throughout the experiment. Further, the development of humoral immune response of the animals was verified. Statistical analysis was carried analysing the effect of isolate and the infection phase. Differences between percentages encountered through nested-PCR were analysed using the Chi-square test. When significant differences were observed (P<0,05), the groups were compared two by two. The difference between parasite loads, optical density values for IgG1, IgG2a and the relation IgG1/IgG2a between the isolates were analysed by the Kruskal-Wallis test. When statistically significant differences were observed (P<0,05), the groups were compared two by two using the Mann-Whitney U test. In blood and lungs, the parasite was detected mainly in the acute phase (P<0,05). The DNA of N. caninum was also detected in the brain mainly in the chronic phase (P<0,05). On comparing parasite loads between isolates, statistically significant differences were observed between them in the chronic phase (P< 0,05). Antibodies of class IgG1 and IgG2a were detected starting from day 16 P.I. and 4 P.I. respectively, increasing gradually and remaining high until day 64 P.I. An analysis of the relation IgG1/IgG2a demonstrated predominance of IgG2a on day 8 e 16 P.I. and highest levels of IgG1 were detected on day 32 and 64 P.I. The isolate NC-Goiás 1 is the first isolate obtained in Goiás and the first obtained from an infected calf, though clinically healthy, reported from South América. These results are the first of a study of the diversity of the protozoon, N. caninum, and indicate that these isolates are of low pathogenicity in mice as compared with other known isolates